MEKANISME PEMBERIAN PROGRAM JAMINAN KECELAKAAN KERJA PADA NASABAH PT. ASABRI PERSERO CABANG PALEMBANG - Sintia Sintia; Meriyati Meriyati (Jurnal Ilmiah Mahasiswa Perbankan Syariah (JIMPA), 2021)
Insurance is one of the financial instruments which is an important part in smoothing the nets of a nation's development. Currently, insurance has entered a global scale competition. PT. ASABRI (Persero) is a state-owned company engaged in special insurance for the TNI, members of POLRI and PNS DEPHAN / POLRI whose task is to improve the welfare of state apparatus through insurance and pension payments. The existence of ASABRI stems from the problem of differences in military characteristics for the participation of TNI Soldiers, Polri Members, and the Ministry of Defense / Polri PNS (there is no PPPK) which was originally a participant in Taspen (Savings Fund and Civil Servant Insurance) which was formed on April 17, 1963 based on a Government Regulation Number 15 of 1963. To facilitate insurance management for military participants, based on the idea of the Indonesian Armed Forces (APRI) in this case the Army and the approval of the Minister of Revenue, Financing and Supervision Affairs and the General Governing Body of PN Taspen.